Thank you for the opportunity to help you with your question!
(4u^2+40u+64)/(u^2-2u-8) = 4(u^2+10u+16)/(u^2-2u-8)
and we have :
for the equation : u^2+10u+16 = 0
delta= 100 - 64 = 36
so : u1 = -2 and u2 = 4
so : u^2+10u+16 = (u + 2)(u - 4)
and for the equation : u^2-2u-8 = 0
delta=4 + 32 = 36
so : u1 = -2 and u2= 4
so : u^2-2u-8 = (u + 2)(u - 4)
4(u^2+10u+16)/(u^2-2u-8) = (4(u + 2)(u - 4)) / ((u + 2)(u - 4)) = 4
each time you have any others homework please call me first or invite me or send me a private quesetion i will give you the best answers :
it shows that your answer was wrong
no is not where is wrong
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?